Analisis Kebisingan dengan Menggunakan Peta Kebisingan serta Rekomendasi Program NIHL (Noise Induced Hearing Loss) di PT. Wijaya Karya Beton, Tbk. PPB Pasuruan - Shalina, Nia Vita; Tualeka, Abdul Rohim (Indonesian Society of Applied Science, 2025)
Noise is one of the environmental issues that frequently occurs in the workplace, particularly in the manufacturing industry. Excessive and prolonged exposure to noise can cause health problems for workers, such as Noise-Induced Hearing Loss (NIHL). PT. Wijaya Karya Beton, Tbk. PPB Pasuruan, in its production process, uses various machines and equipment that can produce quite high noise levels. To overcome the noise problem at PT. Wijaya Karya Beton, Tbk. PPB Pasuruan, it is necessary to create a noise description using a noise map, so that monitoring can be carried out. In addition, implementing the NIHL (Noise-Induced Hearing Loss) program is needed to prevent and reduce the risk of hearing loss in workers. This study aims to describe noise using a noise map and provide recommendations for noise control efforts in the form of Noise-Induced Hearing Loss (NIHL). The method used is descriptive observational, with primary data from direct observation and secondary data from noise measurements conducted by PT. Envilab Indonesia. The results of the study showed that noise levels in several production areas exceeded the permitted threshold, with the highest noise intensity reaching 89.7 dBA. Recommendations include the use of ear protection, regular noise monitoring, and worker education on noise hazards. Implementation of the NIHL program is expected to reduce the risk of hearing loss and improve occupational health and safety.